The Internationalisation of E-Commerce Firms - Ducker, Joseph (2018)
The rapid technological advancements and progression of cross border economic integration over the past few decades have had a significant impact on the international business landscape. As a result, many small and medium enterprises (SME’s) have become increasingly active in international markets, a development that has predominantly been enabled through Electronic Commerce. What is of particular interest, is the speed by which these firms have displayed their internationalisation processes. Therefore, this dissertation will examine the foreign expansion of E-Commerce companies (ECCs) through the following question: